Fostering innovation through quantum technology transfer: Insights from the second Vasco Ronchi Colloquium - Cataliotti, Francesco Saverio (Il Colle di Galileo, 2025)
The article presents an in-depth analysis of the topics covered by this second Vasco Ronchi Colloquium (VRC), held on March 27th 2024 at the Arcetri headquarters of the National Institute of Optics of CNR, entitled “(QU)BITS OF TECHNOLOGY TRANSFER” and focusing on quantum technologies for sensing and security. The VR Colloquia are a format of brief targeted meetings, designed specifically by CNR-INO for boosting the interaction between researchers from the institute and businesses with an effective approach which could trigger the start of a collaboration aimed at the technology transfer of the research results. The two VRCs experienced at CNR-INO have proven effective in capturing corporate interest and initiating collaborations for the transfer of technologies to the market, both with lower and higher TRLs. The fields of application of quantum technologies developed at CNR-INO and presented here range from biomedical imaging to next-generation sensors, to new data encoding methods for secure applications and transmissions. The experience of a spin-off in the reference sector that participates in the VRC serves as an important example of successful technology transfer in this specific market. At the same time, the VRC provides a valuable opportunity for spin-offs, offering a boost for potential new trade connections and opportunities for collaboration with entrepreneurs.